The Road to Wicked The Marketing and Consumption of Oz from L. Frank Baum to Broadway - Drummond, Kent (Springer International Publishing, 2018)
The Road to Wicked examines the long life of the Oz myth. It is both a study in cultural sustainability- the capacity of artists, narratives, art forms, and genres to remain viable over time-and an examination of the marketing machinery and consumption patterns that make such sustainability possible. Drawing on the fields of macromarketing, consumer behavior, literary and cultural studies, and theories of adaption and remediation, the authors examine key adaptations and extensions of Baum's 1900 novel. These include the original Oz craze, the MGM film and its television afterlife, Wicked and its extensions, and Oz the Great and Powerful-Disney's recent (and highly lucrative) venture that builds on the considerable success of Wicked. At the end of the book, the authors offer a foundational framework for a new theory of cultural sustainability and propose a set of explanatory conditions under which any artistic experience might achieve it.